2012
DOI: 10.1590/s0104-11692012000600020
|View full text |Cite
|
Sign up to set email alerts
|

Interference of nail polish on the peripheral oxygen saturation in patients with lung problems during exercise

Abstract: AIM: To assess the interference of nail polish on the reading of peripheral oxygen saturation in patients with chronic obstructive pulmonary disease on the step exercise. METHODS: In this study, there was the inclusion of patients with chronic obstructive pulmonary disease, current non-smokers, of both sexes. Four different colours of nail polish were used in the present study (base, light pink, red and brown), randomly distributed among the fingers of the right hand, with the corresponding fingers on the oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Shimoya et al had a study on 42 patients with stable COPD using 4 different colors of nail polish to observe the effect of SpO2. Their result was light pink and red color nail polish did not affect SpO2 readings 18. …”
mentioning
confidence: 85%
“…Shimoya et al had a study on 42 patients with stable COPD using 4 different colors of nail polish to observe the effect of SpO2. Their result was light pink and red color nail polish did not affect SpO2 readings 18. …”
mentioning
confidence: 85%
“…[23] Privileges of pulse oximetry for assessing oxygenation of patients are safety, low expense, no need of specialist, short time results, and no need of blood sampling. [24]…”
Section: Introductionmentioning
confidence: 99%
“…Although pulse oximetry is simple, it may give incorrect and unreliable results (diagnostic errors) in some conditions such as oxygen saturation below 70%, nail polish, environment light (e.g., operation lamp, florescent lamp, fiber devices), movement of sensor, incompatibility of sensor with device, shock with decline in tissue perfusion, skin pigmentation, carboxy hemoglobin, methemoglobin, anemia, raised blood lipids, raised blood bilirubin, no calibration of device, and intravenously injected dye. [45] Since pulse oximeter probes are most commonly applied over the fingernails, it has been a concern that nail polish may hinder light transmission. [6] Some studies indicated clinically significant decline in oxygen saturation (5%–10%) due to nail polish,[789] whereas some of them have demonstrated the accuracy of pulse oximetry measurement even with black, blue, and purple nail polish.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation